Rapid-Stretch Injury to Peripheral Nerves: Histologic Results. Issue 3 (29th May 2019) - Warner, Wesley S; Yeoh, Stewart; Light, Alan; Zhang, Jie; Mahan, Mark A
Abstract: BACKGROUND: Although most severe peripheral nerve injuries result from high-speed mechanisms, there is no laboratory model to replicate this clinical condition. OBJECTIVE: To qualitatively and quantitatively describe microanatomical injury of rapid stretch. METHODS: The sciatic nerves of 36 Sprague-Dawley rats were subjected to rapid-stretch nerve injury, using fixed-direction strain produced via constrained weight drop applied to an intact nerve. Nerve injury severity was categorized by biomechanical parameters. Injury to nerve microarchitecture was quantified with serial longitudinal sectioning, with specific focus on the endoneurium, perineurium, and epineurium. RESULTS: Four grades of stretch injury severity were determined by mathematical cluster analysis: sham, elastic stretch, inelastic stretch, and stretch rupture. Two patterns of injury to endoneurial architecture were quantified: loss of fiber undulation (straightened fibers) and rupturing of individual fibers ("microruptures"). Straightening of nerve fibers was the earliest accommodation to stretch injury and accounted for elongation during elastic stretch. Microruptures were distributed along the length of the nerve and were more severe and involved greater volume of the nerve at higher biomechanical severity. Epineurium and perineurium disruption increased in frequency with progressive injury severity, yet did not predict transition from one injury grade to another ( P = .3), nor was it a hallmark of severe injury. Conversely, accumulation of microruptures provided strong correlation to nerve injury severity (Pearson's R = .9897) and progression to mechanical failure. CONCLUSION: Nerve architecture is injured in a graded fashion during stretch injury, which likely reflects tissue biomechanics. This study suggests new considerations in the theoretical framework of nerve stretch trauma.